Overplaying-Welfarism and Social Security: The Case of the Karnataka Building and Other Construction Worker’s Welfare Board - Gangadhara, Manjunath (Christ University Law Journal, 2023)
The Union Ministry of Labour and Employment notes that the unorganized sector of workers constitutes about 93% of India’s labour workforce. Despite the presence of a vast majority- the role of welfare policies and their impact on the unorganised labour workforce has largely been unascertained. This can be seen with the exclusion of unorganised workers with the various benefits under the new labour codes, despite substantive recommendations by the Parliamentary Standing Committee on Labour on the same. The Building and Other Construction Workers (Regulation of Employment and Conditions of Service) Act, 1996 provides for the establishment of State Welfare Boards that use the construction cess collected to formulate various welfare schemes for the benefit of construction workers. The Supreme Court in the year 2012 expressed grave concerns about the ineffective utilization of funds by the State Welfare Boards, and in this regard, a Model Welfare Scheme was formulated in 2016. Using data from the annual reports of the Karnataka Building and Other Construction Workers Welfare Board-this paper finds glaring inconsistencies in the current schemes formulated by the Karnataka Building and Other Construction Workers Welfare Board, such as the inclusion of schemes not envisaged under the Model Welfare Scheme and not meeting the necessary conditions envisaged under the Model Welfare Scheme to name a few. The paper compares the schemes along with the ILO’s Convention 102 on Social Security- asserting that despite India being a non-signatory to the convention- its mandate on the minimum standards of social security needs to be followed. Such disparity in the formulation of welfare schemes not only ensures that the intended beneficiaries of such schemes continue to be left out of the result of welfare, but it also adds an unnecessary burden on the State both in terms of expenditure and resources. The paper recommends significant policy reforms such as the removal of schemes contrary to both the Model Welfare Scheme and the ILO Convention 102 on Social Security and larger transparency on scheme-wise expenditure for better implementation of welfare schemes by the Karnataka Building and Other Construction Workers Welfare Board.